Effect of folic acid combined with docosahexaenoic acid intervention on mild cognitive impairment in elderly: a randomized double-blind, placebo-controlled trial - Li, Mengyue; Li, Wen; Gao, Yiming; Chen, Yongjie; Bai, Dong; Weng, Jinxi; Du, Yue; Ma, Fei; Wang, Xinyan; Liu, Huan; Huang, Guowei (European journal of nutrition, 2021)
Purpose This study aimed to assess the effects of folic acid (FA) combined with a docosahexaenoic acid (DHA) intervention on the cognitive function and inflammatory cytokines in elderly subjects with mild cognitive impairment (MCI). Methods This randomized, double-blind, placebo-controlled trial recruited 240 individuals with MCI in Tianjin, China, and randomly allocated into 4 groups: FA + DHA (FA 800 μg/d + DHA 800 mg/d), FA (FA 800 μg/d), DHA (DHA 800 mg/d), and placebo. Cognitive function, serum folate and homocysteine (Hcy), plasma DHA and inflammatory cytokines levels were measured at baseline and 6 months. Results Daily oral FA, DHA and their combined use for 6 months significantly improved the full-scale intelligence quotient (FSIQ) and some subtests of Wechsler Adult Intelligence Scale compared to the placebo. The increases of FSIQ, arithmetic, picture completion scores in the FA group and picture completion, block design scores in the DHA group were significantly less than that in the FA combined DHA group ( P < 0.05). Meanwhile, daily oral FA, DHA and their combined use for 6 months significantly decreased plasma inflammatory cytokines compared to the placebo. The changes of interleukin-1β levels in the FA group and interleukin-6 levels in the DHA group were significantly less than that in the FA + DHA group ( P < 0.05). Conclusions Daily oral FA, DHA and their combined use for 6 months can significantly improve cognitive function and decrease plasma inflammatory cytokines in MCI individuals. The combination of FA and DHA was more beneficial than each individual nutrient on their own.